Efeito anti-inflamatório e anticonvulsivante do Canabidiol durante duas fases do ciclo estral de ratas no modelo de crise convulsiva induzida por PTZ - Janisset, Nilma do Rocio Lara de Lima [UNIFESP] (2019)
Cannabidiol (CBD) is one of the major cannabinoids present in Cannabis sativa with great therapeutic potential. According to evidence from preclinical and clinical studies, CBD was shown to have anticonvulsive effect and has recently been proposed for the treatment of epileptic seizures. Approximately 70% of women with epilepsy face additional challenges on seizures exacerbation due to hormonal changes that occur during the menstrual cycle. Given the impact of hormonal influences on seizure activity and potential complications of treatments, the goal of the present study was to investigate the influence of two phases of the estrous cycle of female rats on the protective effect of CBD in seizures induced by pentylenetetrazole (PTZ). Wistar female rats in the estrus (E) and diestrus (D) phases were treated with vehicle (CTRL) or CBD (50mg/kg). One hour after CBD treatment, acute generalized seizures were induced by administration of PTZ (60mg/kg), and the following parameters were recorded: mortality, latency, duration and quantity of seizures. After 24h, half of animals from each group were perfused and their brains processed by immunohistochemistry for the microglial marker Iba-1, and in the other half, blood was collected for the analysis of the pro-inflammatory interleukin IL-1β levels. Behavioral parameters of seizure and inflammatory responses were analyzed and the results suggested that CBD have protective effects in estrous phase by reducing the mortality rate and quantity of seizures. Additionally, CBD in estrous phase reduced acute inflammatory responses altering the pattern of microglia expression and interleukin levels. Our findings indicated that CBD has distinct anticonvulsive effects in the two estrous cycle phases, altering the inflammatory response that occurs after acute seizures. The present results indicate that, this protective effect is influenced by hormonal variations, showing prominent effect during the estrus phase. Our study may help to clarify some issues related to the therapeutic potential of CBD in catamenial epilepsy and may contribute to the development of new therapies in the future.